Relationship of serum 25-hydroxyvitamin D [25(OH)D] concentration with diabetic patients attending BIRDEM Hospital, Dhaka - Islam, Tanzida; Rahman, Md Maruf Ur; Begum, Wazeda; Saha, Santwana; Shumi, Shamima Islam; Sarker, Fatema (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Epidemiologic studies have shown that low vitamin D levels are associated with reduced insulin sensitivity and increased risk of developing type 2 diabetes mellitus. Many studies have been reported that serum concentration of vitamin D are lower in type 2 diabetic patient and non diabetic patient also in relation to age, sex, occupation, dietary intake and sun exposure. Objectives: The present study was aimed to assess the serum 25-hydroxyvitamin D concentration [25(OH)D] among adult population attending BIRDEM hospital with and without type 2 diabetes mellitus and also find out the relationship between the deficiency of vitamin D and development of type 2 diabetes mellitus. Materials and Methods: It was an analytical cross sectional study where around 250 subjects were taken purposively and among them, 200 were type 2 diabetic subjects and 50 were non diabetic. Study was conducted at BIRDEM hospital within the age group 18 to 65 years from January 2015 to December 2015. Data about socio-demographics were collected, blood pressure, height, weight were measured and BMI were calculated. Glycaemic status was assessed by HbA1c% and plasma glucose level. Vitamin D was measured by HPLC and SPSS (17) was used for t-test, chi-square test, ANOVA & Pearson's correlation coefficient test. Anthropometric and Biochemical parameters were collected by pre-questionnaire from the record book of the patient. Results: The percentage of low serum 25-hydroxyvitamin D concentration [25(OH)D] was significantly higher in type 2 diabetics than non diabetics, that was 55.5% vs 20% (p value <.001). Patients with poor glycaemic control had a higher percentage of low 25(OH)D status (64.1%) where vitamin D level <20 ng/ml than those of vitamin D level >20ng/ml ( 35.9%). There was no significant difference of fasting blood glucose and serum 25-hydroxyvitamin D [25(OH)D] concentration. By using Pearson's correlation coefficient (r) result showed a significant inverse relationship between serum 25(OH)D concentration and 2 hours after breakfast and HbA1c in type 2 diabetic subjects (r =-0.241,-0.225; p=0.071, 0.001 respectively). Patient with a diabetic duration more than or equal 5 years had low vitamin D level (p=.001). A statistically negative correlation of 25(OH)D level with HbA1c in type 2 diabetic patient, (r=-257, p <.001). Moreover HbA1c was found as a significant predictor for vitamin D status in our body. There was no statistical significance was noticed in the mean value of [25(OH)D] with age, sex and BMI of type 2 diabetic subjects. Conclusion: Vitamin D deficiency tends to increasing in type 2 diabetic patients. This may reflect the additive effect of glycaemic control on vitamin D status. Considering this higher percentage of low vitamin D level among T2DM patient, a strategy should develop in our health care facility for providing vitamin D to the population especially those with type 2 DM. J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 23-28